Danske arkæologer i Den persiske Golf - Glob, P.V. (Kuml, 1960)
Danish Archeologists in the Persian Gulf. The excavations in the sheikhdoms of Kuwait, Bahrain, Qatar and Abu Dhabi were continued from the middle of January to about the first of April 1960 by large force of archeologists, with the author as leader and Geoffrey Bibby as deputy leader. In Kuwait investigations were resumed on Failaka 8th January under the overall direction of Poul Kjærum. At the "tell" of Sa’ad on the southwest corner of the island excavation of the town site from the end of the Third Millennium 1) was continued by Oscar Marseen, assisted by Kristen Møllenhus of Trondheim, Peter Seeberg and Aino Kann Rasmussen, and here a large number of small dwelling rooms were uncovered to the south, and to the north remains of larger buildings, badly destroyed in the course of stone-plundering (Fig. 1). In the tell of Sa’id close by the excavation of the temple from the 3rd century BC, which had already been identified 2), was completed by Professor Kristian Jeppesen, Steffen Fisker, Thorkild Hansen and Elsebeth Sander Jørgensen, while Erling Albrectsen continued the excavation of the fortifications which surround this site and the associated buildings 3). Immediately to the north of this site excavation was commenced on a tell which proved to cover the foundations of imposing buildings from the end of the Third Millennium, topped by later levels, by Karl Vibe Müller of Oslo and Jens Aarup Jensen. In addition Gunnar Lange-Kornbak look part in the expedition as conservator and Lennart Larsen as photographer, while Kuwait’s museum was represented by Tareq Rajab and Imran Abdo. The excavations of the temple and of a coin hoard are separately reported (p. 187 and 205), while of the other objects discovered special mention must be made of some 150 stamp-seals of steatite of the same type as those previously found 4), as well as cylinder seals, several of which bore cuneiform inscriptions. The succes of the expedition and its economic basis were the result of generous support from the Ruler of Kuwait, His Highness the Emir Abdullah Al-Salim Al-Sabah, the Minister of Education, His Excellency Sheikh Abdullah Al-Jabir Al-Sabah, and the Director of Education, Abdulaziz Hussein, and by the practical assistance of the Deputy Director, Darwish Miqdadi, and of Ahmed Al-Eisa. In Bahrain the excacations of previous years were continued from 10th January at the prehistoric capital at Qala’at al-Bahrain, where Hans Berg and Karen Frifelt uncovered the eastern part of the large palace-building 5), while E. Kerrn Lillesø and Svend Bue-Madsen commenced an investigation of the western portion of the city wall, which here proved to be exceptionally well preserved (Fig. 2). Hellmuth Andersen and Peder Mortensen continued the investigation of the temples at Barbar, where the run of the western and northern walls of the three building phases was finally determined 6). The investigation of flint sites in the southwestern desert of Bahrain was also continued, and two burial tumuli near the village of Sar were excavated by Knud Thorvildsen and Arne Thorsteinsson, and proved to contain lron-Age stone cists in full man’s length. These tumuli were shown to have been built up in several stages, extended to the sides by the placing of new graves, producing the irregular shape and flat top by which these mounds are distinguished from the large number of conical tumuli from the Third Millennium in Bahrain’s desert 7). This flat type of tumulus is found in large numbers close to the west coast villages of Dumistan, Karzakkan and Shaharakkan, which would appear to suggest that these villages were founded at the same time as the tumuli. Frode Visti was in charge of the camp and of conservation, while the artist, Karl Bovin, was the guest of the expedition for two months. The excavations on Bahrain were made possible, as in earlier years, by grants from the Carlsberg Foundation, the Government of Bahrain and the Bahrain Petroleum Company, and the work was as usual followed with great interest by the Ruler of Bahrain, His Highness Sheikh Sulman bin Hamad Al-Khalifah, the heir-apparent, His Excellency Sheikh Isa bin Sulman Al-Khalifah, by the Secretary to the Government, G. W. R. Smith, and by the Vice President of Bapco M. H. Lipp. In Qatar a thorough investigation was carried out of the southwestern coastal areas of the peninsula, where previously a number of flint sites had been found at Al-Hamlah and Ras Uwainat Ali 8). Here Holger Kapel and Hans Jørgen Madsen worked from 14th January, and found 40 new flint sites from Paleolithic and Neolithic periods. All were surface sites (Fig. 3), but a very large body of material was collected, particularly from a Neolithic site south of Dukhan, where about 200 surface-flaked arrowheads were collected 9), together with a large number of axes and scrapers. The investigations were carried out with means provided by the Government of Qatar and the Qatar Petroleum Company, and with the generous assistance of the Ruler, His Highness Sheikh Ali bin Abdullah Al-Thani, the Adviser to the Government, G. M. Hancock, the Chief of Police, Commandant R. Cochrane, and the General Manager of Q.P.C., P.R.A. Ensor. On the island of Umm an-Nar in Abu Dhabi the investigation of the stone tumuli was continued from 25th January by Knud Thorvildsen and Arne Thorsteinsson, who excavated two large and several small tumuli 10). They proved to contain very complicated grave structures with skeletons, beads and painted pottery from the Third Millennium, covered by corbelled vaults of cut stone, some of which, by the southern entrance to the largest of the mounds, bore reliefs of bulls, camels, snakes and other animals (Fig. 4). The Ruler, His Highness Sheikh Shakbut bin Sultan bin Zaid, and His Excellency Sheikh Zaid bin Sultan bin Zaid freely gave their permission for the investigation, which they followed with great interest, while for the practical arrangements for sojourn on a completely desert island the thanks of the expedition are due to the local representative of Abu Dhabi Marine Areas, Ian Cuthbert. P. V. Glob